MitoQ Modulates Lipopolysaccharide-Induced Intestinal Barrier Dysfunction via Regulating Nrf2 Signaling - Shengfeng Zhang; Qingniao Zhou; Youcheng Li; Yunli Zhang; Yinmei Wu (Hindawi Limited, 2020)
Background. Gut barrier dysfunction with alterant mucosal permeability during sepsis is a challenge problem in clinical practice. Intestinal epithelial cells (IECs) are strongly involved in mucosal oxidative stress and inflammatory response. The current study aimed at investigating the effect of MitoQ, a mitochondrial targeted antioxidant, in the treatment of intestinal injury and its potential mechanism during sepsis. Methods. 30 minutes before sepsis induction by lipopolysaccharide (LPS) treatment, mice were treated with MitoQ. Intestinal histopathology, mucosal permeability, inflammatory cytokines, and mucosal barrier proteins were evaluated in the present study. Results. MitoQ pretreatment significantly decreased the levels of plasma diamine oxidase, D-lactate, and intestinal histological damage and markedly restored the levels of tight junction proteins (ZO-1 and occludin) following LPS challenge. Furthermore, MitoQ inhibited the LPS-induced intestinal oxidative stress and inflammatory response, evidenced by increased levels of intestinal superoxide dismutase and glutathione, and decreased levels of intestinal IL-1, IL-6, TNF-α, and nitric oxide levels. Mechanically, we found that MitoQ inhibited the oxidative stress via activating nuclear factor E2-related factor 2 (Nrf2) signaling pathway and its downstream antioxidant genes, including HO-1, NQO-1, and GCLM. Conclusions. MitoQ exerts antioxidative and anti-inflammatory effects against sepsis-associated gut barrier injury by promoting Nrf2 signaling pathway.